2001
DOI: 10.1111/j.1365-2621.2001.tb15219.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Zein Coating and Sorbic Acid to Reduce Listeria monocytogenes Growth on Cooked Sweet Corn

Abstract: Several proteins, lipids and waxes were tested as edible coatings on sweet corn. Only zein, a natural constituent of corn, gave a continuous adhesive and stable coating with satisfactory sensory properties. After 8 days at 10 °C, the population of L. monocytogenes was 10-fold lower on coated sweet corn than on non-coated sweet corn indicating a barrier effect of zein coating. Sorbic acid was incorporated in the coating at a concentration required to inhibit L. monocytogenes growth (approximately 1 mg sorbic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…2007). Coating thickness, adhesion, continuity and the KS release rate are important factors in determining fungi inhibition of the antimicrobial edible coatings (Carlin et al . 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2007). Coating thickness, adhesion, continuity and the KS release rate are important factors in determining fungi inhibition of the antimicrobial edible coatings (Carlin et al . 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The adhering thickness of the coatings depend on viscosity, concentration and density of the biopolymer solution as well as draining time, chemical composition, surface properties of the coating solutions and the surfaces being coated (Cisneros-Zevallos and Krochta 2003). Furthermore, the release rate of KS from the coating depends on the type of chemical binding between KS and the biopolymer coating (Carlin et al 2001;Kuorwel et al 2011). Therefore, antifungal effectiveness of edible coatings is related to differences in chemical and physical characteristics (Arfa et al 2007;Suppakul et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the addition of antimicrobial plant extracts such as essential oils [4] or of food preservatives such as sorbic acid [5], nisin [6] or lysozyme [7] in biodegradable materials has been proposed. According to Appendini and Hotchkiss [8], traditional ways used for active packaging are: (i) addition of sachets/pads containing volatile antimicrobials into packages, (ii) coating or adsorbing antimicrobials onto polymer surfaces (postthermomechanical processing of polymers operations to obtain antimicrobial packaging materials include for instance enduction [9], soaking [10], spraying [11], or plasma deposition [12] treatments to deposit antimicrobial agents or coatings thereon), (iii) immobilization of antimicrobials to polymers by ionic or covalent linkages, and (iv) incorporation of volatile and non-volatile antimicrobial agents directly into the polymer bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Zein, alcohol-soluble maize protein (prolamins), has bland flavor (Carlin, Gontard, Reich, & Nguyen-The, 2006) and has been studied as a carrier polymer for a variety of bioactive compounds (Chen, Gross, Yuan, & Talashek, 2002;Zhong, Jin, Xiao, Tian, & Zhang, 2008;Zhong & Jin, 2009). Particularly relevant to this work, spray drying was used to encapsulate lysozyme, an antimicrobial protein naturally occurring in foods such as hen egg white, in zein capsules in our earlier study, and an appropriate spray drying formulation resulted in capsules that demonstrated sustained release of lysozyme over 49 days at pH 6.0 (Zhong & Jin, 2009).…”
Section: Introductionmentioning
confidence: 99%